Attitudes to noise and behaviour towards hearing protection among Pasifika university students in New Zealand. (3rd July 2021) - Reddy, Ravi; Nosa, Vili; Mafi, Ilaisaane; Welch, David
ABSTRACT: It is estimated that 1.1 billion young people worldwide are at risk of hearing loss due to high levels of noise exposure. Hearing loss can contribute to low self-esteem, poor employment prospects and social problems. The aim of this research was to explore the attitudes and beliefs towards noise, hearing loss and hearing protection among Pasifika university students in New Zealand. 96 Pasifika students completed the Youth Attitude to Noise Scale (YANS) and Beliefs About Hearing Protection and Hearing Loss (BAHPHL) questionnaire electronically using a Qualtrics survey. The findings show that the study sample had similar low mean scores in the BAHPHL scales related to susceptibility to hearing loss, severity of hearing loss, and benefits of preventive action compared to findings of similar international research. This implies that Pasifika participants had more positive beliefs than their international peers on some factors. Despite their greater awareness, the Pasifika sample had poor attitudes related to minimising loud sounds in the daily environment, perceived barriers towards prevention, behavioural intention and social norms towards hearing conservation. This study provides a good foundation to develop a culturally appropriate hearing conservation intervention aimed at improving hearing-health outcomes among young Pasifika people.